Treatment of postoperative sciatic nerve palsy after total hip arthroplasty for postoperative acetabular fracture: A case report. (November 2016) - Kanda, Akio; Kaneko, Kazuo; Obayashi, Osamu; Mogami, Atsuhiko; Morohashi, Itaru
Abstract: Acetabular fracture is usually treated with osteosynthesis. However, in the case of an intra-articular fracture, osteosynthesis can result in arthropathy of the hip joint and poor long-term results, hence, total hip arthroplasty is required. However, in total hip arthroplasty for postoperative acetabular fracture, sciatic nerve palsy tends to develop more commonly than after primary total hip arthroplasty. This is a case report of a 57-year-old Japanese male who had internal skeletal fixation for a left acetabular fracture that had occurred 2 years earlier. One year later, he developed coxarthrosis and severe pain of the hip joint and total hip arthroplasty was performed. After the second surgery, he experienced pain along the distribution of the sciatic nerve and weakness of the muscles innervated by the peroneal nerve, indicating sciatic nerve palsy. We performed a third operation, and divided adhesions around the sciatic nerve. Postoperatively, the anterior hip joint pain and the buttocks pain when the hip was flexed were improved. Abduction of the fifth toe was also improved. However, the footdrop and sensory disturbance were not improved. A year after the third operation, sensory disturbance was slightly improved but the footdrop was not improved. We believe the sciatic nerve palsy developed when we dislocated the hip joint as the sciatic nerve was excessively extended as the hip joint flexed and internally rotated. Sciatic nerve adhesion can occur easily in total hip replacement for postoperative acetabular fracture; hence, adhesiotomy should be conducted before performing hip dislocation to prevent injury caused by nerve tension. The patient agreed that the details of this case could be submitted for publication. The work has been reported in line with the CARE criteria and cite. Highlights: We report a case of total hip arthroplasty for postoperative acetabular fracture with postoperative sciatic nerve palsy. The sciatic nerve palsy tends to develop after total hip arthroplasty following osteosynthesis for acetabular fracture. It would have been beneficial to use MEP, as a decrease in amplitude would have alerted to the need for neurolysis surgery.